Unlocking the spell : a tale of the wide-awake princess - Baker, E. D. (New York : Bloomsbury, 2012)
Princess Annabelle, who is immune to magic and can temporarily reverse spells put on others, encounters various fairy tale characters when she embarks on an expedition into the woods to find a dwarf responsible for turning Sleeping Beauty's prince into a bear.
Sequel to: The wide-awake princess.
School Library Journal, February 2013.
Teacher Librarian, December 2012.
Library Media Connection, January 2013.
School Library Journal.
Teacher Librarian.
Keywords: Princesses -- Juvenile fiction; Magic -- Juvenile fiction; Characters and characteristics in literature -- Juvenile fiction; Fairy tales; Princesses -- Fiction; Magic -- Fiction; Characters in literature -- Fiction; Fairy tales; Fantasy; Princesses -- Fiction; Magic -- Fiction; Characters and characteristics in literature -- Fiction; Fairy tales; Fantasy fiction; Fairy tales; Princesses -- Fiction; Magic -- Fiction; Characters in literature -- Fiction; Fairy tales; Fantasy fiction